Association between peri-implantitis and systemic inflammation: a systematic review - Yan, Yumeng; Orlandi, Marco; Suvan, Jeanie; Harden, Simon; Smith, Jacqueline; D’Aiuto, Francesco (Frontiers in Immunology, 2023)
Background Peri-implantitis is an infectious/inflammatory disease with similar clinical and radiographic features to periodontitis. Overwhelming evidence confirmed that periodontitis causes elevations in systemic inflammatory mediators; this is unclear for peri-implantitis. Hence, this study aimed to appraise all available evidence linking peri-implantitis with systemic inflammation. Methods A systematic review was completed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eight electronic databases (Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, Web of Science, Dentistry & Oral Sciences Source, Scopus, LILACS, and China Online), ClinicalTrials.gov, WHO International Clinical Trials Registry Platform (ICTRP), and gray literature were searched up to February 9, 2023. Human studies of randomized controlled trials, non-randomized intervention studies, cohort studies, case–control, and cross-sectional studies were eligible for inclusion. Quantitative analyses were performed using random effects models. Results A total of 27 full-text articles were retrieved, and 11 clinical studies were included in the final analyses. All evidence gathered demonstrated a consistent association between peri-implantitis and systemic inflammation. Patients with peri-implantitis exhibited higher levels of serum C-reactive protein (CRP) (standard mean difference (SMD): 4.68, 98.7% CI: 2.12 to 7.25), interleukin-6 (IL-6) (weighted mean difference (WMD): 6.27 pg/mL, 0% CI: 5.01 to 7.54), and white blood cell counts (WMD: 1.16 * 103/μL, 0% CI: 0.61 to 1.70) when compared to participants without peri-implantitis. Conclusion Peri-implantitis is associated with higher systemic inflammation as assessed by serum CRP, IL-6, and white blood cell counts. Further research is needed to clarify the nature of this association. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=246837, identifier CRD42021246837.